A imagem de Eva : o governo peronista - Souza, Renata A. Melki de (2016)
This dissertation intends to analyze the image of Eva Perón, between 1939 and e1955 as sources, I'll use the press, Brazilian newspapers, Argentines and the biography 'the Reason of my life,' published in 1951 in Buenos Aires, the other end of this research is to question what was the role of Eva in the Peronist government, which the focus and the look of the press when it comes to the first lady of Argentina and the directions that lead to have this position In addition to show how Perón Argentina is inserted, as the Colonel came to power and the importance of workers for the regime. The work is relevant, therefore, Avoids was one of the most important women of the 20th century, for his performance and his political charisma with the population, also because of the permanence of his memory and Peronism, the papers and biography will be analyzed fully observing its structure, movement, positioning and relations, not only by the news itself. A support frame is the ample bibliography used, that will help me understand how Peronism was organized politically, the political life and work of Maria Eva Duarte and its importance to the polity, workers, trade unions as the basis for the government, its origin and the relationship built even before Perón to the presidency, especially the devotion of Evita, as social action and Justicialism became his reason for living and her enthusiasm for the cause of the humble